If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42 = 7(y + 4) Reorder the terms: 42 = 7(4 + y) 42 = (4 * 7 + y * 7) 42 = (28 + 7y) Solving 42 = 28 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. 42 + -7y = 28 + 7y + -7y Combine like terms: 7y + -7y = 0 42 + -7y = 28 + 0 42 + -7y = 28 Add '-42' to each side of the equation. 42 + -42 + -7y = 28 + -42 Combine like terms: 42 + -42 = 0 0 + -7y = 28 + -42 -7y = 28 + -42 Combine like terms: 28 + -42 = -14 -7y = -14 Divide each side by '-7'. y = 2 Simplifying y = 2
| 2x-10y=16 | | 7X-7=13+3X | | 162=0.5t^2 | | 10x+25=21+14 | | 300*1=-16x | | 15=2h^2-3 | | 10x+2=7x+26 | | 6[c+4]=4c-18 | | (4a-1)(a-1)=10 | | 5x-2y=15 | | logx+log(13-x)=1 | | 3x+7=4x+28 | | 3+2b=15 | | (5-2y)4+(3y+15)3=72 | | 6x+5=9x-10 | | -159=-3+6(5x+5) | | -2(5-x)=14 | | 4(2x-10)=8(x-5) | | 5x-5(-2x-10)=-100 | | -2n+3n-6n= | | 5x-157=-4x+50 | | 72=30-6x | | 6(2x-8)=96 | | 6w+3=8w-3 | | -58=4x+6(-3+2) | | -104=7x+2(2x+14) | | x-5y+12=0 | | -2+x/7=4 | | .01x=3 | | -5x+74=-70-11x | | 6[f+5]=2f-8 | | 3x^3-19x^2+33x=9 |